ANALISIS KESALAHAN PENGGUNAAN TANDA BACA DALAM PEMBELAJARAN BAHASA INGGRIS SISWA - Bella Asih Pratiwi (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2019)
This research is about the error analysis of using punctuation mark by EFL students.  The objectives of this research are to know the most error of using punctuation marks by the EFL students, the error punctuation trend made by the students, and the affecting factors of error in using punctuation mark in writing task. This research will picture the information about the factors affecting the students error in their writing paper and present about the description about the data from the error in students writing paper. The method of this research is qualitative and the data are taken from the students writing task by documentation lecturer and interview at two universities. They are IAIN Metro and Muhammadiyah University of Metro which consist of three participants in each institution. The reseacher concludes that the EFL students hardly understand in using punctuation mark. The reseacher found the error approximately more than 70% in using capitalization. By the interview, the reseacher found some factors such as lack of balance in the curriculum, knowledge, concentration and carelessness, practice.Keywords: Aspect of writing, Error Punctuation, Punctuation.